Regeneration success and early growth of forest stands and selected papers from an IUFRO Conference held in Copenhagen in June 1996 - Skovsgaard, J.P.; Vanclay, J.K. (1997)
Ten papers from the full proceedings of the above conference providing results of more complete work on the diverse aspects of regeneration and early growth. The conference discussed the theme broadly and encompassed theoretical and applied aspects, plantation and 'close-to-nature' silviculture, natural and plantation forests, in tropical, temperate and boreal zones. The papers contained in this special issue of Forest Ecology and Management reflect this broad perspective in both species and regional focus.